PROSES ADOPSI INOVASI PERTANIAN SUKU PEDALAMAN ARFAK DI KABUPATEN MANOKWARI – PAPUA BARAT - Mulyadi Mulyadi; Basita Ginting Sugihen; Pang S. Asngari; Djoko Susanto (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2007)
Although the agriculture activities has been introduced for relatively a long time, the subsistent agriculture of the Arfak Tribal Group has still dominated in their agriculture system. In their agriculture activities, the new innovations has been adopted for a short time. The new innovations to be seen as a disturbance to their conservative norms. But this theory disagreed by Boef et al. (1993:206) as noted that the conservative system is not the cause but the top down agriculture program which contradicted with the local norms. This research are aimed to:(1) Identify the factors influencing the adoption process by the Arfak tribal group.(2)Identify the perceptions of the Arfak people about the agriculture innovations and extension education which they received from the government.(3) Identify the social culture values (norms, traditional system, custom) both the supporting and the obstructing the farm of Arfak people. The research used survey method and participation observation. Data are analized by proportion analysis and Structural Equation Model (SEM). The results of the research showed that:(1) The social capital which supported the innovations adoption process by the Arfak tribe are emphaty ability, cosmopolitant behaviour, creative and innovative ability.(2) There are significant correlation between the Arfak people with their learning needs, social culture, and responsive behavior of extension education launched by the government officials